2020
DOI: 10.1002/cssc.201903182
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Investigation of the Role of the Anchoring Group on Perylene Monoimide Dyes in NiO‐Based Dye‐Sensitized Solar Cells

Abstract: The anchoring group of a sensitizer may strongly affect the overall properties and stability of the resulting dye‐sensitized solar cells (DSSCs) and dye‐sensitized photoelectrosynthetic solar cells (DSPECs). The properties of seven perylene monoimide (PMI) dyes have been comprehensively studied for their immobilization on nanocrystalline NiO film. The PMI dyes differ only by the nature of the anchoring group, which are: carboxylic acid (PMI‐CO2H), phosphonic acid (PMI‐PO3H2), acetyl acetone (PMI‐acac), pyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 67 publications
(135 reference statements)
0
24
0
Order By: Relevance
“…665,666 Typically, carboxylic acid anchoring groups are used; however, until recently, there has been little research into whether or not this is the best choice. 687 Alternative anchoring groups have been proposed, including pyridine, 571,626,650,667,668 di(carboxylic acid)pyrrole, 669,670 hydroxamic acid, 671 di(carboxylic acid)triazole, 638 catechol, 622 carbodithioic acid, 622 methyl phosphonic acid, 622 acetylacetone (acac), 668,672 alkoxysilane, 188 coumarin, 673 aniline, 668 phosphonic acid, 668 hydroxyqinoline, 668 and dipicolinic acid. 668 Phosphonic acid is one of the strongest binding groups and is resistant to both acid and base, but can present some synthetic challenges.…”
Section: Sensitizersmentioning
confidence: 99%
See 3 more Smart Citations
“…665,666 Typically, carboxylic acid anchoring groups are used; however, until recently, there has been little research into whether or not this is the best choice. 687 Alternative anchoring groups have been proposed, including pyridine, 571,626,650,667,668 di(carboxylic acid)pyrrole, 669,670 hydroxamic acid, 671 di(carboxylic acid)triazole, 638 catechol, 622 carbodithioic acid, 622 methyl phosphonic acid, 622 acetylacetone (acac), 668,672 alkoxysilane, 188 coumarin, 673 aniline, 668 phosphonic acid, 668 hydroxyqinoline, 668 and dipicolinic acid. 668 Phosphonic acid is one of the strongest binding groups and is resistant to both acid and base, but can present some synthetic challenges.…”
Section: Sensitizersmentioning
confidence: 99%
“…687 Alternative anchoring groups have been proposed, including pyridine, 571,626,650,667,668 di(carboxylic acid)pyrrole, 669,670 hydroxamic acid, 671 di(carboxylic acid)triazole, 638 catechol, 622 carbodithioic acid, 622 methyl phosphonic acid, 622 acetylacetone (acac), 668,672 alkoxysilane, 188 coumarin, 673 aniline, 668 phosphonic acid, 668 hydroxyqinoline, 668 and dipicolinic acid. 668 Phosphonic acid is one of the strongest binding groups and is resistant to both acid and base, but can present some synthetic challenges. 668,673 Odobel et al and Gibson et al compared the charge-transfer dynamics at the dye/NiO interface for a number of anchoring groups and found that the anchoring group did not significantly influence the rates.…”
Section: Sensitizersmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in order to more quantitatively estimate the spatial extent of a photo‐induced charge transfer, the D CT index has been used. Developed by some of us, 48 it quantifies the length of the hole–electron separation due to a charge transfer excitation computed as the distance of the hole and electron charge density distributions baricenters (R+ and R−, respectively). DCT=||R+R More details and examples of application can be found in Mashietto et al 49 and Farré et al 50 …”
Section: Computational Detailsmentioning
confidence: 99%